Survival and growth of mangrove oyster Crassostrea gasar (Dautzenberg, 1891) reared at different depths in ponds in Benin (West Africa). - LALEYE, PHILIPPE A. (My University, 2022)
The objective of this work was to study the survival and growth of juveniles of the oyster Crassostrea gasar reared in ponds at different depths. Rearing trials were carried out for 42 days (6 weeks) in two ponds (12 m2 x 1.10 m deep), one of which was fertilized with poultry droppings and the other with no fertilization. For each pond, 03 depths (30 cm, 60 cm and 90 cm) were tested in duplicate. At each depth, two iron mesh bags (40 cm x 20 cm x 10 cm) were used. Oysters with an average size of 40.50 mm and average weight of 15.36 g were cultivated at a density of 30 individuals per bag. Phytoplankton density, pH, temperature, transparency and salinity of the water were daily measured between 7:00 and 8:00 am. Oysters were counted weekly. Individual length and weight were measured to evaluate their survival and growth. The values of physico-chemical parameters measured during this study met the requirements of tropical water oysters. After 6 weeks of rearing, the best survival rates were observed at 60 cm in the ponds (86.67% and 81.67% in the fertilized and unfertilized ponds, respectively) while the lowest survival (46.67% and 41.67 in the fertilized and unfertilized ponds, respectively) was recorded at 90 cm depth. The highest mean final sizes (40.584 mm and 40.568 mm in the fertilized and unfertilized ponds respectively) were recorded at 60 cm depth while the lowest values (40.557 mm and 40.553 mm in the same order) were recorded at 90 cm depth. The average final weight ranged from1 5.32 g (at 90 cm depth) to 15.38 g (at 60 cm) while it overlapped between 15.3 g (90 cm depth) to 15.35 g (30 cm depth) in the unfertilized pond. The average daily gain was 0.0004 g/day and 0.0005 g/day respectively for the 30 cm and 60 cm depths of the fertilized pond. The best zootechnical performance was recorded between 30 cm and 60 cm depth in the fertilized pond. Fertilized pond culture highlight future prospects for the promotion of Crassostrea gasar oyster culture in controlled environment.
Keywords: mangrove oyster; crassostrea gasar; phytoplankton; survival; growth; culture